Religions and Ideologies that Promote Common good - John Selvaraj, M. (University of jaffna, 2024)
Religion and ideologies can play significant roles in promoting the common good by providing ethical frameworks, guiding moral values, and fostering a sense of community and solidarity. Here are some ways in which religion and ideologies contribute to the common good: Moral and Ethical Guidance: Many religions offer moral and ethical guidelines that encourage individuals to act in ways that benefit the greater good; Community Building: This sense of community can lead to collective efforts to address social issues and promote the well-being of all members; Charitable and Philanthropic Activities: Religious organizations often engage in charitable activities, providing aid to the less fortunate and contributing to community development. Church encyclicals play a significant role in shaping the Catholic Church’s teachings and perspectives on various issues, including social justice. The Quran, the holy book of Islam, addresses a wide range of topics, including principles related to social justice. Many verses in the Quran emphasize the importance of fairness, compassion, and equity in human interactions. Hinduism, one of the oldest religions in the world, is characterized by a rich diversity of beliefs, practices, and philosophies. Buddhism, as a spiritual and philosophical tradition, refers to the fair and equitable distribution of resources, opportunities, and privileges within a society. My research aims at studying the contributions of different religions for the common good of humanity.
Keywords: Ethical guidance; Community building; Philanthropy